2011
DOI: 10.1007/s11095-011-0518-2
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Poor Tabletability of Pharmaceutical Crystals by Surface Modification

Abstract: HPC coating by spray-drying profoundly enhances tabletability of acetaminophen. This strategy is expected to have transformative effects on formulation development of poorly compressible drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 38 publications
5
39
0
Order By: Relevance
“…The results ( Figure S1) indicate that the crystal structure in all samples is monoclinic polymorph I. The change in peak intensities is attributed to the preferred orientation (Shi and Sun, 2011). Temperature and enthalpy of fusion of acetaminophen and ALD coated acetaminophen samples are summarized in Table S1.…”
Section: Dscmentioning
confidence: 99%
See 2 more Smart Citations
“…The results ( Figure S1) indicate that the crystal structure in all samples is monoclinic polymorph I. The change in peak intensities is attributed to the preferred orientation (Shi and Sun, 2011). Temperature and enthalpy of fusion of acetaminophen and ALD coated acetaminophen samples are summarized in Table S1.…”
Section: Dscmentioning
confidence: 99%
“…Drug powders are used to create enteral drug dosage forms (such as tablets, capsules, pellets and granules), inhalation powders, parenteral injectable preparations, topical transdermal patches and emulsions, as well as ophthalmic systems such as contact lenses and eye drops. Pharmaceutical manufacturing can benefit from improved surface characteristics of powders that optimize drug loading efficiency and improve powder processability (Ghoroi et al, 2013;Shi and Sun, 2011;Vanhoorne et al, 2014;Ehlers et al, 2009;Sauer et al, 2013;Jallo et al, 2015;Beach et al, 2010). Quite often there is a need to stabilize the desired solid state of the API.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In another example, 40% of another highly compressible polymer is insufficient for forming an intact tablet with poorly compressible acetaminophen. 6 A tablet, however, cannot be too big (usually less than 1 g) for easy swallowing and compliance by patients. 7 Consequently, this strategy of simply adding highly compressible excipients to a formulation is unfit for drugs that must be delivered in a high dose.…”
mentioning
confidence: 99%
“…We previously showed that coating particles with a layer of highly bonding polymer is effective in improving powder tabletability of extremely poorly compressible powders. 5,6 When coated with a layer of plastic and highly bonding material, large bonding area can develop irrespective of the deformation mechanism of the original particles. Surface coating delivers highly bonding excipients where they are most needed in the tablet, that is, at the particle-particle contact points ( Fig.…”
mentioning
confidence: 99%